The Effect of Mucosal Flap Technique in External Dacryocystorhinostomy on Surgical Success: “H” Flap Versus “U” Flap - Gunduz, Abuzer; Cumurcu, Tongabay; Demirel, Soner; Ozsoy, Ercan (Annals of Medical Research, 2021)
None